Resistência bacteriana e o uso indiscriminado de antibióticos na atenção primária - Mariana de Melo Paião; Tainá dos Santos Silva; Eduarda Deganutti Casarin; Rogelio Rocha Barros (Revista ft, 2026)
Antimicrobial resistance occurs when bacteria develop mechanisms that enable them to survive the action of antibiotics that were previously effective. In primary health care, which constitutes the gateway to the healthcare system, the rational use of antibiotics remains a persistent concern. These medications are often prescribed without adequate diagnostic confirmation or in response to social pressures and patient demands. In this context, the aim of this study was to investigate, through the scientific literature, the relationship between the indiscriminate use of antibiotics in primary health care and the increase in bacterial resistance, as well as to identify strategies for the rational use of these medications. An integrative literature review was conducted, including searches for articles published between 2015 and 2025 in the PubMed, SciELO, and Virtual Health Library (BVS) databases. A total of 14 studies, with different methodological designs and conducted in various countries, were included in the review. The results demonstrated that factors associated with inappropriate antibiotic prescribing in primary health care encompass not only clinical aspects but also social, cultural, and structural dimensions of healthcare systems. It is concluded that the indiscriminate use of antibiotics in primary health care is directly associated with the increase in bacterial resistance.